I'JAZ AL-ILMY OF THE QUR'AN: SCIENTIFIC ANALYSIS OF SURAH THAHA 77 WITH FLUIDA DYNAMIC APPROACH - Idris Idris; Muslihun Muslihun; Fanisar Pradini (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2022)
Al-Qur'an is God's word, which many types various, one that discusses the previous Prophet's history is called Tarikh. Out of Quran's History, able to teach people after it. Alquran is a Prophet Muhammad's miracle and miracle to a person who thought it. The violence case in the Quran was called mukjizat or I'Jaz. One of the signs of science is in history. In Prophet Musa, who split the sea into two, this story is in SURAH Thaha: 77. So this journal will discuss 1) I'jaz al-Tarikhy in Surah Thaha: 77, 2) From history, then analysis by science to found I'Jaz al-‘Ilmy in this verse. The result will be obtained by starting at the story; this proves that Prophet Musa and his miracle of splitting the sea can own because this is evidenced by analyzable.